Control of DC Motor Using Integral State Feedback and Comparison with PID: Simulation and Arduino Implementation - Ma'arif, Alfian; Rahmat Setiawan, Naufal (Journal of Robotics and Control (JRC), 2021)
The Direct Current (DC) motor is widely applied in various implementations. The main problem in the DC motor is controlling the angular speed on the specific reference. This research then proposed an integral state feedback design for tracking control in DC motor, with Simulink Matlab simulation and the Arduino hardware implementation. The results will be compared with the implementation of the PID controller. The integral state feedback controller can handle the system to reach the setpoint with good performance in the simulations, even with changing different poles and setpoints. In the hardware implementation, the current sensor (INA219) and encoder sensor are used since all state variables need to be calculated. Based on the result, the controller can reach the setpoint stably with oscillation. Similar results are showed in simulations with different setpoints. Compared with the PID Controller, the integral state feedback controller has a better response with faster rise time and faster settling time.